Crossroads, religation and other formative loops to face globalization from the view of adolescents [Entre la encrucijada, la religación y otros tipos de bucles formativos para enfrentar la globalización desde los adolescentes] (2015)
Being an adolescent, given the complexity, contradictions and paradoxes configured as an expression through the sociocultural ethos, is not something that can be taught or covered from educative institutions or from education in general, unless a transdisciplinary perspective is assumed. This perspective must take into account the necessity of including the dialectical poles that characterize this in an endless process of consciousness development which, at the end, is just the unlearning process of our ignorance on the adolescence issue, in order to advance towards the re-learning required. This is the point of view of this article, aiming to advance in the debate about the formative condition of teachers to achieve a real social inclusion process and where education has a crucial historical role. The article is derived from a macro research project in progress since 2000 and from which several sides have been showing advances, aiming to enrich the educative logics and the pedagogical practices of institutions with their consequences in terms of formation biases for this population.